Star identification robust to angular rates and false objects with rolling shutter compensation. (January 2020) - Schiattarella, Vincenzo; Spiller, Dario; Curti, Fabio
Abstract: This paper addresses the problem of star identification in the presence of high slew rates, false objects and image deformations introduced by the rolling shutter. These problems can affect the operating life of star trackers and worsen the nominal performances. The proposed methodology relies on a technique named Improved Multi-Poles Algorithm, especially designed for robustness to false objects and slew rates. Angular velocities up to five degrees per second are considered so that stars are seen no more as near-circular spots but appear as streaks. The image deformation due to the rolling shutter of modern active pixel sensor detectors is compensated by means of a mathematical model based on a first order approximation of problem. A star tracker high fidelity simulator generates the input images considering typical noises due to the electronics and space environment. The reported results show that the proposed approach guarantees a reliable star identification and attitude determination with angular velocity from zero to five degrees per second. Highlights: Star identification performed with slew rates, false objects and APS deformation. Robustness to false objects guaranteed by the Improved Multi-Poles Algorithm. A rolling shutter compensation model is proposed to consider image deformation. The results are obtained using a high-fidelity star tracker simulator. Reliable star identification guaranteed with angular rate from 0 to 5 deg/sec.